Data Driven Organizational Culture and Managerial Cognition Reshaping Decision Authority Capability Development and Governance Structures in Algorithmic Environments - Muhamad Fahrezi (Universitas Komputer Indonesia, 2026)
The rapid expansion of artificial intelligence, big data analytics, and algorithmic decision systems has transformed organizational structures and decision processes. This study analyzes how data-driven organizational culture and managerial cognition jointly reshape decision authority, capability development, and governance structures in algorithmic environments. Using a narrative literature review, the research integrates perspectives from strategic management, organizational theory, information systems, and digital governance to develop a comprehensive conceptual framework. The findings show that a data-driven culture promotes evidence-based norms that encourage managerial cognitive adaptation toward probabilistic reasoning and analytics literacy. This cognitive shift legitimizes decentralized yet algorithmically bounded decision authority characterized by shared human–machine accountability. Structural transformation further requires hybrid capabilities combining data literacy, cross-functional integration, and governance competence. Governance redesign institutionalizes oversight mechanisms that reinforce cultural alignment through continuous learning. The study advances understanding of the socio-cognitive foundations of algorithmic transformation and provides strategic guidance for building adaptive, accountable organizations in data-intensive environments.